The Influence of E-Wom on Purchase Decisions is Mediated by The Brand Image of Laptop Products on Consumers in E-Commerce - Zul Yusri, Hilman; Sikki Manggabarani, Alfatih; Assumpta Wikantari, Maria (Quantitative Economics and Management Studies, 2025)
This study aims to influence of e-wom on purchase decisions is mediated by the brand image of laptop products on consumers in e-commerce. This type of research is quantitative. The purposive sampling method was used in this study. This study uses a type of quantitative data quantitative data is a type of numerical data that can be analyzed with statistics, to prove the hypothesis set. This research uses primary and secondary data sources. Primary data was collected by distributing a questionnaire to online laptop buyers via Google Form that included factors such as their purchase decisions, brand image, and e-wom. Secondary data from several journals related to the research subject. This study analyzes laptop buyers, especially those who make purchases through the internet, which occur in the three largest online marketplaces in Indonesia. The researcher used non-parametric inferential statistics with SmartPLS version 4.0. E-WOM has a significant influence on laptop purchase decisions in e-commerce. This indicates that e-WOM is an element that increases consumers' decision to choose laptops sold in Indonesian e-commerce. Brand image has a significant influence on laptop purchase decisions in e-commerce. This means that brand image is a factor that increases consumer decisions to buy laptops in Indonesian e-commerce. E-WOM has a significant influence on purchasing decisions through laptop brand image in e-commerce.